Economics of marigold cultivation in some selected areas of Bangladesh (Bangladesh Journal of Agricultural Research, 2013)
Marigold cultivation is now a profitable enterprise to the farmers, but the socioeconomic data and information of this flower are very scarce in Bangladesh. Therefore, the study was conducted to identify agronomic practices, analyze relative profitability, and input-output relationship during February 2011. Primary data were collected from 100 randomly selected farmers from Jessore and Jhenaidah districts. The results indicated that 95% farmers cultivated T- 004 line and only 5% farmers cultivated T- 003 line of marigold. The per hectare costs of marigold cultivation were Tk. 1,47,234 and Tk. 1,02,858 on full cost and variable cost, respectively. The major share of full cost was for human labour (34%), land use (18%), fertilizer (15%), and irrigation (10%). The yield of marigold was 2,650,447 flowers per hectare. The gross margin and net return were Tk.1, 62,186 and Tk.1, 17,812 per hectare, respectively. The net return was 81% higher than lentil, 85% higher than mustard, and 6% lower than potato cultivation. The benefit cost ratios were 2.57 and 1.80 on variable cost and full cost basis, respectively. Cobb-Douglas production function revealed that human labour, land preparation, seedling, urea, TSP, MoP, and irrigation had positive effect on marigold cultivation. The lack of technical knowledge, nonavailability of high yielding variety, and infestation of insects and diseases were major problems for marigold cultivation. Therefore, necessary steps from concerned authority are needed to overcome these problems. DOI: http://dx.doi.org/10.3329/bjar.v37i4.14395 Bangladesh J. Agril. Res. 37(4): 711-720, December 2012